The Financial Settlement of the Failing Banks and Credit Institutions with a Look to the Comprehensive Banking Plan - Ahmad Beygi Habibabadi; Hussein Pashaei (آموزه‌‌های فقه مدني)
The main reason of the financial crisises (failures) and credit institutions fails to fulfil their obligations. The ancient system strategy for overcoming this crisis is to use bankruptcy process. Today, the legal thoughts tend toward this to throw away the normal system of bankruptcy for preventing the exacerbation of the financial crises and to think the social, economic necessities to get the highest efficiency by the less expenditure. The financial resolution system has planned different tools to maintain the financial stability of banks and has allowed to early intervention of the supervisor authorities. Also, in the situation of failure to recovery, the deposit guarantee provides the assurance of the depositors. From the other side, it should be considered other legal regulation such as justice and fairness in insolvency and the Volcker Rule. Therefore, in this note we are going to identify this mentioned system and draw the weaknesses and strengths and to accord with the comprehensive banking plan of Islamic Republic of Iran.